TRADISI RITUAL SOSIAL: RUANG PERJUMPAAN LINTAS ETNIS DAN AGAMA - Faisal Faisal (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2020)
A number of structural and cultural efforts by the government and society continue to be made to instill multicultural awareness. One that has recently emerged is the urgency of meeting spaces that bring people across ethnicities and religions. Meeting spaces can be created in various forms of activity. However, a number of traditions in various regions that have taken place so far have functioned as meeting spaces. That social capital has become the glue of integrity across ethnicities and religions, without coercion and feeling of being disadvantaged by one another. This paper is a limited research that shows a number of social ritual traditions that flow beyond ethnic and religious boundaries and function as spaces of encounter. In the midst of the still problematic diversity for some communities, looking further and deeper, improving functions and preserving these social ritual traditions are very important to accompany various government programs in strengthening national harmony and integrity.